On pricing futures options on random binomial tree - Ganikhodjaev, Nasir; Bayram, Kamola (Institute of Physics Publishing (UK), 2013)
The discrete-time approach to real option valuation has typically been implemented in the finance literature using a binomial tree framework. Instead we develop a new model by randomizing the environment and call such model a random binomial tree. Whereas the usual model has only one environment (u, d) where the price of underlying asset can move by u times up and d times down, and pair (u, d) is constant over the life of the underlying asset, in our new model the underlying security is moving in two environments namely (u1, d1) and (u2, d2). Thus we obtain two volatilities σ1 and σ2. This new approach enables calculations reflecting the real market since it consider the two states of market normal and extra ordinal. In this paper we define and study Futures options for such models.